EFFECTS OF SELENIUM AND α-TOCOPHEROL ON QUALITY AND FERTILISING ABILITY OF SPERMATOZOA IN EXTENDED COCK SEMEN (2017)
Spermatozoon apoptosis in extended semen is a challenge to artificial insemination in poultry production. Chicken spermatozoa undergo damages in vitro due to lipid peroxidation among other factors. Extender supplementation with exogenous antioxidants could mitigate lipid peroxidation and improve semen quality. However, inclusion of antioxidants such as selenium and α-tocopherol in semen extender to improve quality of sperm cells has not been adequately documented. Therefore, effects of selenium and α- tocopherol on quality and fertilising ability of spermatozoa in extended cock semen were assessed. Semen samples were collected from fifteen Lohmann breeder cocks aged 30 weeks, pooled and divided into nine groups. Each group was extended with Ringers Solution (RS) without antioxidant (T1), RS with α-tocopherol at 25 (T2), 50 (T3), 75 (T4) or 100μgmL-1 (T5) and selenium at 25 (T6), 50 (T7), 75 (T8) or 100μgmL-1 (T9). Another set of semen was harvested, pooled and extended with RS (TA), RS+25μgmL-1 α- tocopherol (TB), RS+25μgmL-1 selenium (TC), RS+12.5μgmL-1 α-tocopherol+12.5μgmL- 1 selenium (TD), RS+25μgmL-1 selenium+25μgmL-1 α-tocopherol (TE) were assessed in vitro and in vivo. All treatments were evaluated at room temperature (RT: 27-29 ᵒC) and refrigeration (4-6 ᵒC) at interval of 3h until motility dropped below 50%. Spermatozoa Progressive Motility (SPM), Spermatozoa Liveability (SL), Total Antioxidant Capacity (TAC, mmol/L) and Lipid Peroxidation (LP, MMDA/l06 Spermatozoa) were determined using standard procedures. Seventy-five Lohmann breeder hens aged 40 weeks were divided into five groups and inseminated with each of the treatments under RT and another seventy-five under refrigeration for the in vivo evaluation. Egg fertility and hatchability were recorded weekly for four weeks. Data were analysed using descriptive statistics, correlation and ANOVA at α0.05. At RT, the highest SPM (91.7±1.1%) and SL (94.5±1.0%) at 3h were recorded in T5 and least at T7 (78.3±1.1%) and T9 (83.2±1.0%), respectively. The TAC ranged from 2.0±0.14 (T9) to 3.2±0.14 (T5), while LP ranged from 0.5±0.28 (T1) to 2.8±0.28 (T7). Under refrigeration, SPM was lower in T4 (55.0±0.8%) than other treatments at 6h. The UNIVERSITY OF IBADAN LIBRARY iv highest SL (95.7±1.5%) was recorded in T3 and least in T6 (80.8±1.5%), while TAC was highest in T9 (2.7±0.07) and least in T1 (1.9±0.07). Effect of α-tocopherol and selenium combinations under RT was similar among treatments for SPM, SL and LP up to 6h. Under refrigeration, SPM and SL were highest at TE (95.0±1.9% and 96.5±1.1%, respectively) and least at TD (76.7±1.9% and 87.0±1.2%, respectively), while TAC and LP were unaffected by the combinations. At RT, egg fertility was higher at TA (86.5±7.3%), TC (86.0±7.6%) and TD (82.0±5.0%) than TB (57.0±7.1%) and TE (72.3±8.7%), while hatchability of set eggs ranged between 40.0±8.8% (TB) and 71.3±10.2% (TC). Fertility positively correlated with hatchability (r=0.95). Under refrigeration, egg fertility ranged between 35.3±12.4% (TB) and 54.3±10.0% (TD), while hatchability was lowest at TA (20.3±6.8%) and highest at TD (49.0±14.8%). α-tocopherol at 100μgmL-1 enhanced cock semen quality, but combination of α- tocopherol and selenium did not in vitro at room temperature. Selenium inclusion at 25μgmL-1 under room temperature improved hatchability in Lohmann breeder hens. Keywords: Artificial insemination, Lipid peroxidation, Selenium, α-tocopherol, Egg fertility. Word count: 500